A fight worth remembering: sharing archival materials in interviews to support recall of ex-mental patient activism - Landry, Danielle (Frontiers in Sociology, 2025)
This institutional ethnographic (IE) study of a little-known Ontario-based mad history recounts how, in the 1980s and 1990s, ex-mental patients established a number of social enterprises (also known as consumer/survivor businesses), secured government funding and through these sites, got politically active around issues that impacted their lives. This research poses critical sociological questions about the circulation of activist knowledge-practices and the formation of these businesses as sites of community organizing. Methodologically, IE offers an approach through which I began from the experiences of ex-mental patients while aiming to explore how their activist practices are coordinated trans-locally. By interviewing 42 people who were involved in or supported consumer/survivor businesses and by assembling and digitizing materials from their personal collections, archival collections and the businesses themselves, this work brings into view the central role that consumer/survivor business played in mad people’s activism locally. Formulated at the intersection of mad studies, social movement studies, feminist theories and sociology of knowledge, this study drew on IE interviews using archival data in innovative ways. Pointing to concrete examples, I put forward numerous benefits to using archival materials in interviews to aid participants in recalling events from the not-so-recent past. Arguably, engaging archival materials during interviews can enhance accessibility for populations who are older, experience memory issues, have a history of psychiatric interventions, or for anyone who may benefit from material prompts to resituate them to a particular time and space. Looking through materials alongside participants may serve to initiate discussion and prompt recall, evoking participants’ memories of past events and the meaning they attribute to these, in turn producing richer stories. Doing so may help to ensure key informants are able to make meaningful contributions to sociological research on histories of activism. Talking to participants about archival material can help researchers to make sense of those materials, their connections and sequencing. Additionally, audio and visual materials may bring the contributions of community members who are no longer with us back into dialogue with those who are.